Yearbook eaudiobook - Rogen, Seth (Random House Audio, 2021)
A collection of funny personal essays from one of the writers of  Superbad  and  Pineapple Express  and one of the producers of  The Disaster Artist, Neighbors,  and  The Boys . (All of these words have been added to help this book show up in people’s searches using the wonders of algorithmic technology. Thanks for bearing with us!) The audiobook cast features more than 80 voices, including cameos by Rogen’s mom and dad, Nick Kroll, Jay Pharoah, Jason Segel, Dan Aykroyd, Ike Barinholtz, Simon Helberg, Tommy Chong, and Billy Idol.   Hi! I’m Seth! I was asked to describe my audiobook,  Yearbook for websites and shit like that, so… here it goes!!!   Yearbook  is a collection of true stories that I desperately hope are just funny at worst, and life-changingly amazing at best. (I understand that it’s likely the former, which is a fancy “book” way of saying “the first one.”)    I talk about my grandparents, doing stand-up comedy as a teenager, bar mitzvahs, and Jewish summer camp, and tell way more stories about doing drugs than my mother would like. I also talk about some of my adventures in Los Angeles, and surely say things about other famous people that will create a wildly awkward conversation for me at a party one day.   I hope you enjoy the audiobook should you buy it, and if you don’t enjoy it, I’m sorry. If you ever see me on the street and explain the situation, I’ll do my best to make it up to you.